Participation of Farm Women in Rice Cultivation and Their Training Needs - S.K. Nath and S. Chowdhury, (Indian Journal of Extension Education, 2022)
An investigation was carried out in Balasore district of Orissa during 2007-08 to assess the participation of farm women in rice farming and their training needs. It was conducted among 75 small and marginal types of farm women. It was found that from the seventeen activities involved in rice farming, maximum number of farm women (100%) participate in storage and preservation whereas the least number (0%) in land preparation. Though the participation of farmwomen in insect pest and disease management was found very poor, yet their perception for need of training on the subject secured the second highest rank i.e. behind the variety selection. Majority of the farm women (92%) avail information from the eo-farmers and neighbours. Need of training was found immaterial for most of the farmwomen, was detected as the major constraint in dissemination of knowledge through training.